Analisis Wacana Estetika Bahasa Pidato Upacara Perkawinan Jawa di Yogyakarta dan Hubungannya dengan Pembangunan Karakter - Mulyana, Mulyana (Kementerian Sekretariat Negara Republik Indonesia, 2023)
Javanese wedding ceremonies in Yogyakarta still abundantly use aesthetic aspects in their choice of speech language. Moreover, such aesthetic diction also embodies character building values for its interlocutors. The aims of the first section of this study is to explain the people’s character that will be described comprehensively and clearly in Javanese wedding ceremonies. The second one is to express and explain which particular linguistic elements cause the speech discourse to be imbued with aesthetics of susastra Jawa (Javanese literature). Furthermore, this study also expresses the contexts and their changes that transpire in wedding ceremonies performed by the Javanese people. This study used the sosiolinguistic approach in conjunction with the discourse analysis. This study used the object and/or data of the oral stories from wedding speeches (tanggap wacana) that were gathered and documented all the while as the study was being conducted. The stories utilized as data were documented from the direct stories in wedding ceremonies performed by Javanese interlocutors in the area of Yogyakarta. The results of the data analysis are able to describe and explain several questions posed by this study. First, the spoken languages in the wedding ceremonies of the Javanese people consist of the Javanese, the Indonesian, and a mixture of languages denoted as Jawindo (Javanese-Indonesian). Second, it was successfully found that the aesthethics elements used in the wedding speech discourses consist of: tembung saroja, tembung garba, yogyaswara, keratabasa, tembung entar, paribasan, bebasan, saloka, pepindhan, pralambang, purwakanthi, panambang bunyi ha-, seselan – in-, seselan –um-, tembung kawi, and religious diction. Third, changes in the wedding speech discourses occurred due to changes of the underlying contexts. Finally, the ceremonial discourse in wedding ceremonies can shape the development of a firm mental attitude and character. Keywords: ceremonial discourse, wedding ceremony, character